2020
DOI: 10.1111/jors.12515
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration and informality: Evidence from Peruvian establishments

Abstract: This paper contributes to the emerging literature investigating agglomeration externalities in developing countries and focuses on the less studied differences between the formal and the informal sector. Using establishment‐level data and instrumental variable estimations, we find that both formal and informal establishments benefit from agglomeration externalities. We provide evidence that informal establishment total factor productivity (TFP) increases more with city size than formal establishment TFP. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…We find that the impact of urbanization on the productivity of the services sector is conditioned by the level of development in the country in question, with a positive effect in developed countries and a negative one in developing countries. Our findings add to the recent literature on urbanization without growth in developing countries by addressing the central role that services play in their economies (Ahluwalia, 2016; Bernedo Del Carpio & Patrick, 2021; Chen et al, 2016; Duranton, 2015; Rogerson, 2016; Tanaka & Hashiguchi, 2020; Tran & La, 2018). In both developed and developing countries, the decline in the manufacturing sector has been accompanied by a growth in services: an increasing weight in terms of both employment and GDP (Cuadrado‐Roura, 2021) at a nearly continuous rate.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We find that the impact of urbanization on the productivity of the services sector is conditioned by the level of development in the country in question, with a positive effect in developed countries and a negative one in developing countries. Our findings add to the recent literature on urbanization without growth in developing countries by addressing the central role that services play in their economies (Ahluwalia, 2016; Bernedo Del Carpio & Patrick, 2021; Chen et al, 2016; Duranton, 2015; Rogerson, 2016; Tanaka & Hashiguchi, 2020; Tran & La, 2018). In both developed and developing countries, the decline in the manufacturing sector has been accompanied by a growth in services: an increasing weight in terms of both employment and GDP (Cuadrado‐Roura, 2021) at a nearly continuous rate.…”
Section: Discussionsupporting
confidence: 68%
“…A distinctive element of developing countries is that the services sector favors the creation of jobs that generally require relatively small investments in physical and human capital, and technology (Arouri et al, 2014; Barufi et al, 2016; Fox, 2012; Jedwab, 2013). A large body of evidence (Ahluwalia, 2016; Bernedo Del Carpio & Patrick, 2021; Chen et al, 2016; Duranton, 2015; García, 2019; Harris, 2014; Rogerson, 2016; Tanaka & Hashiguchi, 2020; Tran & La, 2018) demonstrates a low‐quality agglomeration scenario characterized by a large and growing number of informal firms that do not contribute to and do not benefit from agglomeration in developing countries. Businesses have limited access to labor markets due to the lack of complementarity between agglomeration economies and workers' human capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Del Caprio et al (2017) analysed the case of Peru, considering how agglomeration externality reception and generation vary for formal and informal establishments and investigating multiple potential sources of agglomeration externalities. Finally, Matano et al (2020) analysed the incidence of agglomeration externalities in the labour market in Ecuador.…”
Section: The Influence Of Agglomeration On Growth: a Study Of Argenti...mentioning
confidence: 99%
“…In Latin America, a recent study byAlmeida, Neto, and Rocha (2023) showed strong effects in Brazil of own-industry employment on firm creation and new-firm employment within one kilometer that dissipated with distance and disappeared after five kilometers.Distance to the most agglomerated areas of the city may also play a role in the persistence of labor informality. Informal workers can draw major advantages from agglomeration-in fact, studies in Latin America have frequently found larger productivity effects of agglomeration in the informal than the formal sector(Duranton 2016;Bernedo Del Carpio and Patrick 2021; Quintero and Roberts 2022;.4 While the drivers for this difference are still understudied, it is likely related to access to customers. Much of the informal sector consists of non-tradable services, which need to be produced and consumed in the same place.…”
mentioning
confidence: 99%